2013
DOI: 10.3126/saarctb.v10i1.8672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Tuberculosis Among Hiv Positive Patients Attending Ictc In A Tertiary Care Institute In Ahmadabad, A Western City Of India

Abstract: Introduction: In India, tuberculosis is the most common opportunistic infection among HIV positive patients. This study estimates the prevalence of tuberculosis amongst HIV patients in Ahmadabad, Gujarat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…It's closely similar to study done by Mulla et al, (7) Out of 500 patients, 58 were Tubercular HIV seropositive, and 45(77.5%) were male and 12 (20.68%) were females and 1 (1.62%) was TS/TG. Similarly study was found in Naresh Gill et al, 2013 (17) in Mumbai (males 73.8%, females 26.2%), Nayak et al, (2013) (9) in Surat (males 72.73%, females 27.27%), Ragini et al, 2009 in Vadodara (males 68.7%, females 31.3%), Lata et al, 2015 (10) in Akola (Maharastra) (males 63.63%, females 36.36%). In their study had also reported more males than females.…”
Section: Resultssupporting
confidence: 69%
“…It's closely similar to study done by Mulla et al, (7) Out of 500 patients, 58 were Tubercular HIV seropositive, and 45(77.5%) were male and 12 (20.68%) were females and 1 (1.62%) was TS/TG. Similarly study was found in Naresh Gill et al, 2013 (17) in Mumbai (males 73.8%, females 26.2%), Nayak et al, (2013) (9) in Surat (males 72.73%, females 27.27%), Ragini et al, 2009 in Vadodara (males 68.7%, females 31.3%), Lata et al, 2015 (10) in Akola (Maharastra) (males 63.63%, females 36.36%). In their study had also reported more males than females.…”
Section: Resultssupporting
confidence: 69%